Gene polymorphism profiles of drug-metabolising enzymes GSTM1, GSTT1 and GSTP1 in an Argentinian population - Natalia Weich; Alejandro Roisman; Belén Cerliani; Hilda V. Aráoz; Lilien Chertkoff; Silvina M. Richard; Irma Slavutsky; Irene B. Larripa; Ariela F. Fundia (Taylor & Francis Group, 2017)
Background: Glutathione S-transferases (GSTs) are drug-metabolising enzymes involved in biotransformation of carcinogens, drugs, xenobiotics and oxygen free radicals. Polymorphisms of GST genes contribute to inter-individual and population variability in the susceptibility to environmental risk factors, cancer predisposition and pharmacotherapy responses. However, data about GST variability in Argentina are lacking. Aim: The purpose was to determine the prevalence of GSTM1, GSTT1 and GSTP1 polymorphisms in the general population from a central region of Argentina and to perform inter-population comparisons. Subjects and methods: GSTM1 and GSTT1 gene deletions and GSTP1 c.313A > G were genotyped by PCR assays in 609 healthy and unrelated Argentinians. Results: The frequencies of variant genotypes in Argentinians were GSTM1-null (45%), GSTT1-null (17%) and GSTP1-GG (11%). GSTM1-present genotype was significantly associated with GSTP1-AG or GSTP1-GG variants (p = 0.037; p = 0.034, respectively). Comparison with worldwide populations demonstrated that the GST distributions in Argentina are similar to those reported for Italy and Spain, whereas significant differences were observed regarding Asian and African populations (p < 0.001). Conclusion: This study has determined, for the first time, the normative profile of three pharmacogenetically relevant polymorphisms (GSTM1, GSTT1 and GSTP1) in the largest Argentinian cohort described to date, providing the basis for further epidemiological and pharmacogenetic studies in this country.